Comparative analysis of Indicative, Imperative and Subjunctive Moods in English and Uzbek languages. - Akhunova, Nozima (Журнал иностранных языков и лингвистики, 2021)
The following article discusses the ways and problems of expressing mood categories in world linguistics analyzing them between English and Uzbek language. In particular, the article identifies different approaches to the semantic classification of sentences of the moods in both languages.